THE ORIGINS OF MALAYAN COMMUNISM - Yong, C. F. (Ching Fatt) (Strategic Information and Research Development Centre, 2019)
"Malayan Chinese radicalism in the form of anarcho-communism only emerged in 1919. The ideology of anarcho-communism promoted not only the concept of anarchism but also of communism as a panacea for global problems. The arrival of anarcho-communism was followed in the 1920s by three waves of Chinese communism to Malayan shores until the founding of the Malayan Communist Party in mid-April 1930. The MCP struggled grimly for survival during its early years but posed a real threat to British colonial rule from 1936 after it had secured an important power base in trade unions. It also capitalised on rising Chinese nationalism in July 1937 in the aftermath of the Sino-Japanese War, arousing Chinese community sympathies in general and mobilizing Chinese-educated youths, women and intellectuals in particular. The author draws on substantial Chinese and English-language archival sources and oral history evidence from participants in the movement to reconstruct the chequered history of the Malayan communist movement of pre-war years. The present work explores the origins of Malayan communist, analyses the changing ideology and organisations of the Malayan communist movement, unmasks its dramatis personae and assesses the success or otherwise of British colonial control of the MCP and its various affiliates".